The Effect Of Transformational And Transactional Leadership On The Commitment Of Organization, Turnover, And Perfomance (At Baitul Maal Wat Tamwil, The Special Region Of Yogyakarta) - Juhary, Ali; Mardiyana, Noor; Owin Jamasy, Djamaludin (IOSR Journals, 2019)
The reason why leadership style is born is the necessary to accomplish the duty successfully for a a leader. However, becoming a leader of organization, institution, or institute in this era is demanded to be active in collaborating with various leadership style, such as transformational and transactional. In accordance with the effort to keep the existence and development of BMT in the Special Region of Yogyakarta, it will surely depend on who the leader is, how the commitment of the leader on the BMT is done and how the cooperation among leader staffs, and customers to improve the performance and productivity is done. Transactional and transformational leadership styles are two leadership styles that are classified as contemporary styles. Indirectly are two popular leadership styles and are widely applied by leaders in the modern era. On that basis, in order to prepare conditions in modern times, the issue of transformational and transactional leadership becomes important and needs even the conditions practiced by leaders. In this study transformational and transactional leadership styles along with their dimensions, as independent change in their influence on organizational commitment / workers, turnover and productivity. There is a very strong relationship between transformational leadership style and organizational commitment, while transformational leadership with productivity has a weak relationship. In addition there is a strong relationship between transactional leadership style and organizational commitment and turnover, while leadership style with turnover and productivity is a weak relationship.